2022
DOI: 10.1088/2053-1591/ac4881
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lubricant viscosity on the performance of full ceramic ball bearings

Abstract: As a new high-end bearing product, full ceramic ball bearings are favoured in a variety. However, there have been few studies on the lubrication of full ceramic ball bearings. The purpose of this study is to reveal the relationship between the vibration and temperature rise of full ceramic angular contact ball bearings and the lubricant viscosity, and to improve the service life of the bearings. In this study, the effects of lubricant viscosity on the vibration and temperature rise of silicon nitride full cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sun et al investigated the effects of lubricant viscosity on the vibration and temperature rise of silicon nitride full ceramic angular contact ball bearings under different axial loads and speeds. Their results indicate that at the optimal viscosity value of 32 grade, the vibration and temperature rise of the bearings can be minimized to the greatest extent, with no apparent wear on the contact surfaces (Sun et al, 2022). Hei et al evaluated the friction characteristics of the compression ring-cylinder liner conjunction in engines using lubricating oils of different viscosities.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al investigated the effects of lubricant viscosity on the vibration and temperature rise of silicon nitride full ceramic angular contact ball bearings under different axial loads and speeds. Their results indicate that at the optimal viscosity value of 32 grade, the vibration and temperature rise of the bearings can be minimized to the greatest extent, with no apparent wear on the contact surfaces (Sun et al, 2022). Hei et al evaluated the friction characteristics of the compression ring-cylinder liner conjunction in engines using lubricating oils of different viscosities.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2020) proposed a kinetic model of ceramic bearings under limited lubrication conditions and studied the parameters affecting lubrication, which is of guiding significance for improving the performance of ceramic ball bearings. Sun et al (2022) studied the effect of lubricant viscosity on bearing performance and revealed the lubrication mechanism of full ceramic ball bearings. Sun et al (2023a) studied the dynamic characteristics of full ceramic ball bearings under ultra-low temperature conditions and established a model of liquid nitrogen lubrication of full ceramic ball bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Sun Jian studied the frictional lubrication performance of full ceramic ball bearings and found that the lubricant film thickness of full ceramic ball bearings was positively correlated with the bearing speed and negatively correlated with the bearing load. Bearing speed has a relatively large effect on the variation of lubricant film thickness (Sun et al , 2022b). Yao Jinmei studied the lubrication mechanism of full ceramic deep groove ball bearings.…”
Section: Introductionmentioning
confidence: 99%